Implications for Precision Accelerated Clinically Embedded Research (PACER): A novel technology-enabled approach to conducting minimal-risk research in outpatient community healthcare settings. - Emma Friedman; Kelly Nicole Michelson; Shruti Sehgal; Russell Steans; Mohammad Hosseini; Matthew J Baumann; Amanda K Venables; Theresa L Walunas; Justin Starren (PLoS ONE)
Current challenges in the clinical research landscape include insufficient enrollment of study participants, lack of study participant diversity, protracted study progression, and the siloing of research within academic medical centers. Recent advances in technology could minimize barriers to producing effective, timely, and comprehensive clinical research by addressing issues from study design to dissemination of results. Particularly, the Fast Health Interoperability Resources standards and Clinical Decision Support Hooks could support data acquisition, sharing, and expansion of research across organizations and disparate electronic health records. We developed a novel approach, Precision Accelerated Clinically Embedded Research (PACER), that leverages these advances in healthcare technology to integrate very short, minimal-risk research activities into clinical encounters. PACER could enable scalable, efficient, and cost-effective clinical research and has enormous potential. However, PACER also presents potential ethical, sociotechnical, and implementation quandaries. The current study aimed to obtain insights on these matters from relevant individuals. We conducted 47 qualitative semi-structured interviews with patients, clinicians, research experts (individuals involved in developing and conducting research), and bioethicists. We sought participants' perspectives on the potential ethical, sociotechnical, and implementation issues raised by PACER. We identified five key domains: impacts on clinical research, consent, compensation, impacts on people and organizations, and implementation. We examined interview participants' views using bioethical principles of autonomy, justice/fairness, beneficence, and nonmaleficence. While participants had diverse views, these insights highlight important considerations for PACER implementation and suggest areas for future empirical work.